2014
DOI: 10.1111/ffe.12198
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue of rare‐earth containing magnesium alloys: a review

Abstract: A B S T R A C T Lightweighting in ground vehicles is today considered as one of the most effective strategies to improve fuel economy and reduce anthropogenic environment-damaging and climate-changing emissions. Magnesium (Mg) alloy, as a strategic ultra-lightweight metallic material, has recently drawn a considerable interest in the transportation industry to reduce the weight of vehicles due to their high strength-to-weight ratio, dimensional stability, good machinability and recyclability. However, the hexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 143 publications
(684 reference statements)
1
27
0
Order By: Relevance
“…However, some challenges such as poor corrosion resistance and low room-temperature formability limit the widespread structural applications of Mg alloys in the transportation industry. [10][11][12][13][14][15] Recently, a novel process-roll cladding-was considered to improve the corrosion resistance and formability of Mg alloys. 16,17 Specifically, Al-cladding of Mg alloy sheet could combine the superior corrosion resistance and formability of Al with the high strength-to-weight ratio of Mg substrate.…”
Section: Introductionmentioning
confidence: 99%
“…However, some challenges such as poor corrosion resistance and low room-temperature formability limit the widespread structural applications of Mg alloys in the transportation industry. [10][11][12][13][14][15] Recently, a novel process-roll cladding-was considered to improve the corrosion resistance and formability of Mg alloys. 16,17 Specifically, Al-cladding of Mg alloy sheet could combine the superior corrosion resistance and formability of Al with the high strength-to-weight ratio of Mg substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Vickers hardness (HV1) was used to determine changes during heat treatment with approximately 30 indents each, under a load of 1 kg (9.807 N), and the average values are reported. 3-point bending was conducted using a span of 40 mm on 70 × 10 × 8 mm 3 samples at a speed of 1 mm/min (plates were tested in the upright position to guarantee longer crack propagation). Micrographs revealed the microstructure, and with this, the influence of twins and larger precipitates on crack propagation was determined.…”
Section: Methodsmentioning
confidence: 99%
“…Here it is used as the reference material, and is often alloyed with Nd, Y, and Zr to increase creep, fatigue, and corrosion properties. A review by Mirza et al [3] on Mg-RE alloys, on the basis of a higher Gd content for fatigue studies, presented promising results: Effectively weakened crystallographic textures; suppressed twinning; and enhanced fatigue strength. The role of Nd and/or La in Mg10Gd, in the mechanical properties and corrosion behavior during precipitation hardening, is of interest in this study, especially its influence on crack propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Structural components for the transport industry, such as camshaft covers, clutch and transmission housings, intake manifolds, engine blocks, steering components, radiator supports, and automobile wheels, are inevitably subjected to cyclic stresses in service. For this reason, investigation on the fatigue behaviour of both cast and wrought Mg alloys has recently drawn considerable interest [5][6][7][8][9]. Recent studies [7,9,10] have demonstrated that the addition of rare earth (RE) elements, such as Nd, Gd, Y, can remarkably enhance both the tensile and fatigue strength of Mg alloys.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, investigation on the fatigue behaviour of both cast and wrought Mg alloys has recently drawn considerable interest [5][6][7][8][9]. Recent studies [7,9,10] have demonstrated that the addition of rare earth (RE) elements, such as Nd, Gd, Y, can remarkably enhance both the tensile and fatigue strength of Mg alloys. In the case of castings, this improvement was related both to the microstructural refinement and to the decreased size and amount of porosity and inclusions induced by RE elements [7,11,12], while in wrought Mg alloys it seems mainly due to the corresponding weakness of crystallographic textures and the reduction of twinning [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%